2021
DOI: 10.1007/s11257-021-09302-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving accountability in recommender systems research through reproducibility

Abstract: Reproducibility is a key requirement for scientific progress. It allows the reproduction of the works of others, and, as a consequence, to fully trust the reported claims and results. In this work, we argue that, by facilitating reproducibility of recommender systems experimentation, we indirectly address the issues of accountability and transparency in recommender systems research from the perspectives of practitioners, designers, and engineers aiming to assess the capabilities of published research works. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The results of the Cold Start Challenge study in the fact that new users or new items entering the system adapt to changes in existing users or items [Kulkarni et al,2020]. Investigating the relationship between contextual information and how to use them in the recommendation process with MF methods [Bellogín et al,2021] and on the other hand applying the similarity measure in the preferences of the user [Chen et al,2021], demographic data [Natarajan et al,2020], social data [Boratto et al,2021,Ortiz et al,2022, etc. common ways to solve cold start.…”
Section: Rs Methods With Contextual Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the Cold Start Challenge study in the fact that new users or new items entering the system adapt to changes in existing users or items [Kulkarni et al,2020]. Investigating the relationship between contextual information and how to use them in the recommendation process with MF methods [Bellogín et al,2021] and on the other hand applying the similarity measure in the preferences of the user [Chen et al,2021], demographic data [Natarajan et al,2020], social data [Boratto et al,2021,Ortiz et al,2022, etc. common ways to solve cold start.…”
Section: Rs Methods With Contextual Informationmentioning
confidence: 99%
“…A two-level CTLSVD matrix based on refining the properties of items and users based on the Time contextual information due to the slope of the descending gradient to reduce the challenge of sparse data [Fernández-García et al,2022]. Mainly similarity measure of contextual information is used to reduce sparse data [Bellogín et al,2021]. The use of contextual weighting overlaps measure is used to find the amount of contextual similarity.…”
Section: Rs Methods With Contextual Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproducibility. The lack of reproducibility can be a major barrier to achieve progress in AI [134], and recent studies indicate that limited reproducibility is a substantial issue also in recommender systems research [135,136]. Figure 11 shows for how many of the studied technical papers, artifacts were shared to ensure reproducibility of the reported experiments.…”
Section: Category Of Metrics Examplesmentioning
confidence: 99%
“…Some researchers argue that to enhance reproducibility, and to facilitate fair comparisons between different works (either frameworks, research papers, or published artifacts), at least the following four stages must be identified within the evaluation protocol [79]: data splitting, item recommendations, candidate item generation, and performance measurement. In a recent work [11], these stages have been completed with dataset collection and statistical testing. Some of these stages can be further categorized, such as performance measurement, depending on the performance dimension to be analyzed (e.g., ranking vs error, accuracy vs diversity, and so on).…”
Section: Prior Workmentioning
confidence: 99%